PARADIGMA PENDIDIKAN AKADEMIK-SENTRIS DAN DEGRADASI EMPATI PESERTA DIDIK: A SYSTEMATIC LITERATURE REVIEW - Muzari, Ahmad; Iswatiningsih, Daroe (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The contemporary academic-centric educational paradigm, with its overemphasis on academic achievement and high-stakes assessments, has raised concerns about its impact on students' holistic development, particularly on socio-emotional dimensions such as empathy. This study aims to systematically examine the construction of this paradigm in the literature, analyze its influence on the degradation of students' empathy, and formulate effective counter-strategies. Using a Systematic Literature Review (SLR) of 44 relevant journal articles from the last decade, the study found that a dominant academic orientation creates a competitive climate and significant psychological stress, which in turn erodes empathy through academic stress, social comparison, and weakened cooperative relationships. The findings also highlight that the integration of Social Emotional Learning (SEL), the management of a cooperative classroom climate, and the reduction of academic stress are key strategies for restoring the balance between academic achievement and character development. It concludes that a shift towards a more humanistic and balanced approach to education is crucial to prevent the marginalization of empathy in the education system. ABSTRAK Paradigma pendidikan kontemporer yang cenderung akademik-sentris, dengan penekanan berlebihan pada capaian akademik dan asesmen berisiko tinggi, telah memicu kekhawatiran mengenai dampaknya terhadap perkembangan holistik siswa, khususnya pada dimensi sosial-emosional seperti empati. Penelitian ini bertujuan untuk mengkaji secara sistematis konstruksi paradigma tersebut dalam literatur, menganalisis pengaruhnya terhadap degradasi empati peserta didik, serta merumuskan strategi penyeimbang yang efektif. Menggunakan metode Systematic Literature Review (SLR) terhadap 44 artikel jurnal relevan dari dekade terakhir, studi ini menemukan bahwa orientasi akademik yang dominan menciptakan iklim kompetitif dan tekanan psikologis yang signifikan, yang pada gilirannya mengikis empati melalui stres akademik, perbandingan sosial, dan melemahnya relasi kooperatif. Temuan juga menyoroti bahwa integrasi Social Emotional Learning (SEL), pengelolaan iklim kelas yang kooperatif, dan reduksi tekanan akademik merupakan strategi kunci untuk memulihkan keseimbangan antara prestasi akademik dan pengembangan karakter . Disimpulkan bahwa pergeseran menuju pendekatan pendidikan yang lebih humanis dan seimbang sangat krusial untuk mencegah marginalisasi aspek empati dalam sistem pendidikan.